A Novel Approach to Incarcerated Femoral Hernia Repair in A Jehovah’s Witness Patient: A Case Report of Meshless Open Mcvay Repair - Hamza, Naeem (Journal of Medical Health Research and Psychiatry, 2024)
Background: Femoral hernias are a rare but potentially life-threatening condition that requires immediate surgical intervention. Case: We present a unique case report of an incarcerated femoral hernia in a Jehovah's Witness patient who underwent a meshless open McVay repair. The patient's religious beliefs, which prohibit blood transfusions and limit the use of blood products, significantly influenced our surgical approach. Conclusion: We discuss the challenges of operating on Jehovah's Witnesses and highlight the importance of multidisciplinary teamwork in achieving a successful outcome.